The Effect of Anemia Education on Adolescents’ Intention to Undergo Hemoglobin Testing - Yuliana Kurniawati; Dhesi Ari Astuti (Journal of Social and Community Development, 2025)
Anemia remains a common health problem among adolescents, characterized by low hemoglobin (Hb) levels that affect health, academic performance, productivity, and the overall quality of human resources in the future. This study aimed to determine the effect of anemia education on adolescents’ intention to undergo hemoglobin testing at SMP Negeri 1 Gamping, Yogyakarta. The research employed a quantitative approach with a pre-experimental method using a one-group pre-test and post-test design. A total of 36 respondents participated in the study. The instrument used was a questionnaire. The participants, aged 12–13 years, consisted of an equal proportion of males and females. Before the intervention, most respondents (78%) demonstrated a moderate level of intention to undergo hemoglobin testing. After the anemia education intervention, the proportion of respondents with a high level of intention increased from 11% to 22%, while those with a low level of intention decreased from 11% to 8%. The Paired Sample t-Test yielded a Sig. (2-tailed) value of 0.000 (< 0.05), indicating a significant effect of anemia education on adolescents’ intention to undergo hemoglobin testing. The findings suggest that anemia education is effective in enhancing adolescents’ intention to have their hemoglobin levels checked, making it a valuable preventive educational strategy for the early detection of anemia among adolescents.